Detection Of Static Eccentricity Fault In Psh Induction Motor By Using External Magnetic Flux Density - Halem, N.; Zouzou, S. E.; Ghodbane, H. (University of Eloued جامعة الوادي, 2016)
The objective of this paper is to make a clear and thorough investigation about the effectiveness of Motor Current Signature Analysis (MCSA) for detecting default indexes of static eccentricity in (Principal Slot Harmonics) PSH induction motor. The obtained results using traditional technique (MCSA) are compared with spectrums of external magnetic flux density extracted from healthy and faulty motors. The work is carried out with transient finite element method (FEM) simulations considering motor operation under nominal mechanical load, the notching nature of stator and rotor and the non-linearity behavior of ferromagnetic material are taking into account.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: induction motor; static eccentricity; FEM, PSH; MCSA; magnetic flux density.